Mechanical anisotropy behavior of fused deposition modelling ABS - Sulaiman, Suraya; Sulaiman, Shamsuddin; Sheikh Md Fadzullah, Siti Hajar; Mohd Sayuti,; Mohd Ariffin, Mohd Khairol Anuar (2009)
This research is focus on one of rapid prototyping (RP) technologies that is Fused Deposition Modeling (FDM) using polymer-based material specifically Acrylonitrile-Butadiene-Styrene (ABS). RP technologies provide the ability to fabricate initial prototypes from various model materials. FDM is a typical RP process that can fabricate prototypes out of ABS plastic. To predict the mechanical behavior of FDM parts, it is important to understand the material properties of the raw FDM process material and the effect that FDM built parameter have on anisotropic material properties. Using the Design of Experiment (DOE) approach, the process parameter of FDM, build direction was examined. Mechanical anisotropy behaviors of the prototype were investigated via Tensile Test as per ASTM D638-01 and Compression Test as per ASTM D 695-96. Under tensile loading as per ASTM D638-01, it was found that the part produced in axial orientation (0°) possessed the highest tensile strength of 23.81±0.24MPa followed by diagonal orientation (45°) of 16.87±0.27MPa. Whilst the lowest value of tensile strength was observed for transverse orientation (90°) with 11.21±0.05MPa.Under compressive loading as per ASTM D 695-96, the part produced in transverse orientation (90°) possessed the highest compressive strength of 57.48±0.93MPa but lowest stiffness with 0.27±0.02GPa. The axial orientation (0°) possessed the second highest compressive strength with 38.82±0.39MPa and highest stiffness of 0.93±0.01GPa and the lowest compressive strength is 24.40±2.21MPa at diagonal orientation (45°) and the stiffness value is 0.81±0.08GPa. As a conclusion, mechanical anisotropy behavior is observed for parts produced from FDM machine as an effect of different build direction.